2018
DOI: 10.1111/jiec.12773
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Material Stock of Roads: The Vietnamese Case Study

Abstract: Summary This study is a pioneering effort to quantify the materials stocked in the road network of a developing country, Vietnam, and analyze its relationships to the country's recent economic development. National road networks function as capital and infrastructure investments that are necessary catalysts for countries’ development, while requiring the extraction of vast amounts of construction materials for expansion and maintenance causing environmental impacts. However, there has so far been little resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…() measured six kinds of MS in buildings in Taipei with an average figure of 68 t per capita from 1965 to 2014 using a bottom‐up approach. Nguyen, Fishman, Miatto, and Tanikawa () and Schiller et al. () are that few that used a bottom‐up approach at the macro‐level.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…() measured six kinds of MS in buildings in Taipei with an average figure of 68 t per capita from 1965 to 2014 using a bottom‐up approach. Nguyen, Fishman, Miatto, and Tanikawa () and Schiller et al. () are that few that used a bottom‐up approach at the macro‐level.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al. () adopted a bottom‐up approach in estimating four kinds of MS in road infrastructure in Vietnam from 2003 to 2012 with per capita MS of 29 t (United Nations, ). Schiller et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous research, MS has been estimated for single or multiple components of the built environment. For instance, Guo, Hu, Zhang, Huang, and Xiao (2014), in the case of Beijing, and Nguyen, Fishman, Miatto, and Tanikawa (2018), in the case of Vietnam, have investigated road networks only, and Kleemann, Lederer, Rechberger, and Fellner (2016), in the case of Vienna, and Ortlepp, Gruhler, and Schiller (2015), in the case of Germany, have investigated buildings only. The studies that have examined multiple components of the built environment (Han & Xiang, 2013;Huang, Han, & Chen, 2016;Tanikawa & Hashimoto, 2009;Tanikawa et al, 2015;Wiedenhofer et al, 2015) have indicated that the largest stock is accumulated in buildings that takes between 43 and 90% of the total MS depending on which and how many of the built environment components are analyzed.…”
mentioning
confidence: 99%